Mathematical Creative Thinking Leveling on Non-Mathematics Department Students - Flavia Aurelia Hidajat; Cholis Sa’dijah; Susiswo Susiswo; Sudirman Sudirman; Abdur Rahman As’ari (Jurnal Pendidikan Sains, 2018)
Abstract: This paper seeks to explore and describe a mathematical characteristic of creative thinking level on non-mathematics department students. This paper took 56 college students of Faculty of Economy at University X as a research subject. The data were obtained through the test, interview, and observation. This research dealt with the five existing level and two additional level of creative thinking. The results indicated two additions of creative thinking leveling, namely level 5 which included the ability of students to elaborate ideas and be fluent in various problem solutions; and Level 6 which includes the ability of students to carry out idea elaboration, fluency, and flexibility in a variety of problem-solving strategies. Elaboration of ideas means that students are able to describe, develop previous ideas, and add some new ideas for the solutions generated.Key Words: creative thinking level, creative thinking, non-mathematics studentsAbstrak: Penelitian ini bertujuan untuk mengeksplorasi dan menggambarkan karakteristik tingkat berpikir kreatif matematis pada mahasiswa departemen non-matematika. Penelitian ini mengambil 56 mahasiswa Fakultas Ekonomi di Universitas X sebagai subjek penelitian. Data diperoleh melalui tes, wawancara, dan observasi. Data tersebut berupa deskripsi naratif. Penelitian ini menggunakan lima tingkat berpikir kreatif yang sudah ada dan dua tingkat tambahan. Hasilnya menunjukkan dua penambahan tingkat berpikir kreatif, yaitu tingkat 5 yang termasuk kemampuan siswa untuk mengelaborasi ide dan fasih dalam berbagai solusi masalah; dan tingkat 6 yang mencakup kemampuan siswa untuk melaksanakan elaborasi ide, kelancaran, dan fleksibilitas dalam berbagai strategi pemecahan masalah. Elaborasi ide berarti bahwa siswa mampu menggambarkan, mengembangkan ide-ide sebelumnya, dan menambahkan beberapa ide baru untuk solusi yang dihasilkan.Kata kunci: tingkat berpikir kreatif, berpikir kreatif, mahasiswa non-matematika